Subclavian steal syndrome associated with right aortic arch: A case report - Cai, Jing; Xie, Chao; Wang, Xianwei (Frontiers in Surgery, 2023)
The right aortic arch (RAA) is a rare congenital vascular variant disease. We report a case of subclavian steal syndrome associated with RAA. The main clinical manifestations are vertigo and ischemic symptoms of the left upper extremity. We diagnosed the disease by aortic computed-tomography angiography (CTA) and digital subtraction angiography (DSA). The patient was treated with carotid-subclavian bypass surgery.